المقارنة بين الفعالية الوقائية للفراشي التقليدية و الفراشي المزودة بقضيب نصف ناقل من ثاني أوكسيد التيتانيوم(TiO2) عند اليافعين - نورالله, عبد الوهاب; جبلاوي, أنور (Latakia University Journal -Medical Sciences Series, 2014)
أجريت هذه الدراسة السريرية المتصالبة لمقارنة فعالية استخدام فرشاة الأسنان التقليدية (Oral-B Indicator® Plus ) وفرشاة (®Soladey-eco) المزودة بقضيب نصف ناقل من ثاني أوكسيد التيتانيوم( TiO2) في إزالة اللويحة الجرثومية وتأثيرهما على جراثيم Streptococcus mutans(S.Mutans) لدى اليافعين . شملت العينة 60 يافعاً , تراوحت أعمارهم بين (19-13) سنوات. قسموا إلى مجموعتين , استخدمت الأولى الفرشاة التقليدية والثانية (®Soladey-eco) للتفريش مرتين يومياً لمدة شهر تليه فترة راحة أسبوعين يتم بعدها تبادل المجموعتين لنوعي الفراشي , كما تمت تعمية الفاحص. تم تحديد فعالية كل فرشاة بحساب مشعر اللويحة قبل الاستخدام وبعده ولكلا الفرشاتين لدى جميع أفراد العينة وتم فحص التعداد الجرثومي S.mutans ضمن اللويحة الجرثومية واللعاب قبل وبعد استخدام الفرشاة لنصف العينة فقط . بينت نتائج هذه الدراسة أن فرشاة (®Soladey-eco) أبدت فعالية أكبر في إزالة اللويحة الجرثومية وسببت انخفاضاً أكثر للتعداد العام لجراثيم S.mutans مقارنة مع الفرشاة التقليدية في عينة الدراسة . A clinical trial cross over was carried out to compare the clinical effectiveness of the use of conventional toothbrush (Oral-B Indicator Plus®) and (Soladey-eco®) which is equipped with a rod of semiconductor of titanium dioxide (TiO2) to remove dental plaque and their impact on Streptococcus mutans counts (CFU) . The Sample included 60 patients aged 13-19 years. The sample was equally divided into two groups: the first group used toothbrush (Oral-B Indicator Plus®) and the second used toothbrush (Soladey-eco®) twice daily for one month, followed by (wash out) period for two weeks, after which the exchange of the two groups for the two types of brushes, the examiner was blind. To determine the effectiveness of the two brushes, the dental plaque index was calculated for every brush before and after brushing. The S .mutans (CFU) in saliva was calculated too but just for (n=30) before and after brushing. Results showed that the use of the brush (Soladey-eco®) has greater effectiveness in removing dental plaque and caused a reduction of Streptococcus mutans counts compared with the brush (Oral-B Indicator Plus®) in the research sample